Intestinal helminth co-infection and associated factors among pulmonary tuberculosis patients in Africa and Asia: a systematic review and meta-analysis - Zenebe, Yohannes; Habtamu, Meseret; Abebe, Markos; Tulu, Begna; Atnafu, Abay; Mekonnen, Daniel; Lang, Roland; Munshea, Abaineh (BMC Infectious Diseases, 2023)
Introduction: Tuberculosis (TB) and intestinal helminths have huge public health importance, and they are geographically overlapped. Data about the burden of intestinal helminth and TB co-infection in these areas are fragmented. In this systematic review and meta-analysis we compile the current literatures and generate pooled prevalence. We also identity factors associated with intestinal helminth co-infection among TB patients. Methods: Original articles published in English language up to March 23, 2022 were systematically searched from electronic database (PubMed/Medline, Scopus, Science Direct, Google Scholars and HINARI). The search was done using medical subject heading terms and keywords. Identified articles were exported into the EndNote library. The identified articles were screened using PRISMA flow diagram. Then the methodological quality of included articles was evaluated and rated using the modified version of Newcastle–Ottawa Scale. Data were extracted using Microsoft Excel. Sensitivity analysis and Egger regression test were used for the assessment of heterogeneity and publication bias. Finally the results are presented with a meta-analysis of pooled estimates, forest plots, and tables. The quantitative data were analyzed using Stata version 14. Results: From a total of 5457 searched articles, 22 eligible articles were included in the review. The pooled prevalence of helminth co-infection among TB cases was 29.69% (95%CI: 21.10, 38.29). TB patients were found to more frequently harbor one or more intestinal helminths than TB negative individuals (OR = 1.72 (95%CI: 1.20, 2.48)). Among the reported helminths, Schistosoma mansoni and Strongyloides stercoralis had the highest pooled prevalence among TB cases. However, unlike other individual helminths, only Strongyloides stercoralis (OR = 2.67 (95% CI, 1.20–6.76)) had significant association with TB cases compared to TB negatives. BMI was significantly associated with intestinal helminth co-infection among TB patients (OR = 2.75 (95%CI: 1.19, 6.38)). Conclusions: Patients with TB have been shown to harbor co-infection with one or more intestinal helminths with considerable proportions when compared with TB-negative individuals. The higher prevalence of helminth infection in TB cases might indicate that co-infection promotes active TB disease. Thus, routine intestinal helminth screening and assessment of their nutritional status is suggested for TB patients.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Africa; Asia; Co-infection; Intestinal helminths; Pooled prevalence; Tuberculosis